Perbedaan Hasil Belajar Kognitif Antara Siswa yang Dibelajarkan dengan Model Pembelajaran Learning Cycle 5e dan Learning Cycle 5e-Mind Mapping pada Materi Larutan Penyangga - Rakhmah Marisna; Darsono Sigit (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2018)
Abstract: This study aims to determine the implementation of learning process and student cognitive learning outcomes on buffer material materials using Learning Cycle model 5E-mind mapping and Learning Cycle 5E learning model. This research uses experimental quasi design with posttest only control group design model. The population of this study is all students of grade XI IPA SMAN 5 Malang. The sample of research is class XI G4 as experimental class which was taught by Learning Cycle 5E-mind mapping and class XI F4 as control class which was taught by Learning Cycle 5E. Instruments used in the study include learning instruments (Syllabus, RPP, and LKS) and measurement instruments (Daily Deuteration and Observation Sheets). The results showed that the implementation of Learning Cylce 5E-Mind mapping model has an average of 93.76% and Learning Cycle 5E of 92.90% and there are differences in cognitive learning outcomes among students who are taught by Learning Cycle 5E-Mind Mapping and Learning Cycle 5E. The average cognitive learning outcomes of students who were taught by Learning Cycle 5E-Mind Mapping was 81.13, higher than students who were taught by Learning Cycle 5E that is equal to 75.16